1999
DOI: 10.1021/ic990864p
|View full text |Cite
|
Sign up to set email alerts
|

Is Ferromagnetism an Intrinsic Property of the CuII/GdIII Couple? 1. Structures and Magnetic Properties of Two Novel Dinuclear Complexes with a μ-Phenolato−μ-Oximato (Cu,Gd) Core

Abstract: Two original dinuclear (Cu(II),Gd(III)) complexes (1 and 2) deriving from polydentate nonsymmetrical Schiff base ligands LiH2 have been prepared. Formally they differ by the length of the diamino chain. They crystallize in the orthorhombic Pbca (No. 61) (1) and in the monoclinic P2(1/n) (No. 14) (2) space groups. The cell parameters are a = 12.6295(7) A, b = 20.7894(9) A, c = 18.3301(13) A, and Z = 8 for 1 and a = 12.7246(16) A, b = 13.5691(17) A, c = 14.5310(19) A, beta = 94.629(16) degrees , and Z = 4 for 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 203 publications
(92 citation statements)
references
References 24 publications
8
84
0
Order By: Relevance
“…Jean-Pierre Costes,* Juan Modesto Clemente-Juan, FranÁoise Dahan, Franck Nicode ¡ me, and Marc Verelst Recent papers have shown that the interaction between a gadolinium ion and a second spin carrier (M) is not compulsorily ferromagnetic as suggested earlier for the complexes in which M is an organic radical [1,2] or a metal ion (Cu 2 , [3,4] VO 2 [5] ). Moreover, little attention has been paid to the fact that the Gd ¥¥¥ Gd interaction, which is a particular case of Gd ¥¥¥ M interactions, was found to be antiferromagnetic in all the complexes reported by now.…”
Section: Unprecedented Ferromagnetic Interaction In Homobinuclear Erbmentioning
confidence: 94%
“…Jean-Pierre Costes,* Juan Modesto Clemente-Juan, FranÁoise Dahan, Franck Nicode ¡ me, and Marc Verelst Recent papers have shown that the interaction between a gadolinium ion and a second spin carrier (M) is not compulsorily ferromagnetic as suggested earlier for the complexes in which M is an organic radical [1,2] or a metal ion (Cu 2 , [3,4] VO 2 [5] ). Moreover, little attention has been paid to the fact that the Gd ¥¥¥ Gd interaction, which is a particular case of Gd ¥¥¥ M interactions, was found to be antiferromagnetic in all the complexes reported by now.…”
Section: Unprecedented Ferromagnetic Interaction In Homobinuclear Erbmentioning
confidence: 94%
“…3, 5 These pure heterodimetallic systems open new perspectives for (i) the exploration of interactions between f-and d-block ions possessing first-order orbital momenta, [5][6][7][8] (ii) the preparation of extended and organised heterotrimetallic d-fd 14 and f-d-f 15 architectures in the solid state and (iii) the detailed re-examination of the intimate mechanism proposed by Goodenough.…”
Section: -58mentioning
confidence: 99%
“…In other words, the magnetic orbitals centered on Gd(III) and Cu(II) must have a fairly large overlap density on the oxygen atom, which can be obtained only through a fairly substantial covalency of the Gd-O bond [1,12,28,[30][31][32] Owing to the difficultes in analysing the magnetic properties of (Cu, Ln) pairs involving a Ln(III) ions, which possesses a first-order orbital moment [27], we restricted ourselves to consider only (Cu , Gd) complex. Acorrding to J.-P. Costes et al [27] and O. Kahn et al [12] for the 4f 1 -4f 6 configurations of Ln 3+ , angluar and spin moment are antiparallel in 2S+1 L J free-ion ground state (J = L -S) ( where S, L and J, are the spin, orbital and total quantum numbers, respectively). A parallel alignment of the Cu 2+ and Ln 3+ spin momenta would lead to an antiparallel alignment of the angular momenta, that is to an overall antiferromagnetic interaction.…”
Section: Resultsmentioning
confidence: 92%
“…From a magnetic point of view, well isolated dinuclear complexes have a great advantage for they only contain the Cu-Gd interaction parameter. On the contrary, in complexes of higher nuclearity, as in trinulcear Cu 2 Gd complexes for example, we have to take into account the desired Cu-Gd interaction but also a possible Cu-Cu interaction (antiferromagnetic, ferromagnetic or equal to zero) [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%